Association between pancreatic fat and incidence of metabolic syndrome: a 5‐year Japanese cohort study. Issue 12 (17th May 2018) - Yamazaki, Hajime; Tauchi, Shinichi; Kimachi, Miho; Dohke, Mitsuru; Hanawa, Nagisa; Kodama, Yoshihisa; Katanuma, Akio; Yamamoto, Yosuke; Fukuma, Shingo; Fukuhara, Shunichi
Abstract: Background and Aim: Previous cross‐sectional studies showed that pancreatic fat was associated with metabolic syndrome. However, no longitudinal study has evaluated whether people with high pancreatic fat are likely to develop future metabolic syndrome. This study investigated the association between baseline pancreatic fat and metabolic syndrome incidence. Methods: In 2008–2009, 320 participants without metabolic syndrome underwent health checks, which included unenhanced computed tomography, and were followed up annually for 4–5 years. Baseline pancreatic fat amounts were evaluated using a histologically validated method that measured differences between pancreas and spleen attenuations on computed tomography. The participants were divided into low (reference), intermediate, and high pancreatic fat groups based on pancreas and spleen attenuation tertiles. Metabolic syndrome incidence was evaluated annually over a median follow‐up period of 4.99 (interquartile range, 4.88–5.05) years, in accordance with the 2009 harmonized criteria. Risk ratios (RRs) for the association between baseline pancreatic fat amounts and metabolic syndrome incidence were estimated using Poisson regression models adjusted for age, sex, body mass index, liver fat, pre‐metabolic syndrome, cigarette use, alcohol use, and physical activity. Results: Metabolic syndrome incidence was 30.6% (98/320). Pancreatic fat was associated with an increased incidence of metabolic syndrome, based on a univariate analysis (RRs [95% confidence interval], 3.14 [1.74–5.67] and 3.96 [2.23–7.03] in the intermediate and high pancreatic fat groups, respectively). The association remained statistically significant in the multivariate analysis (RR [95% confidence interval], 2.04 [1.14–3.64] and 2.30 [1.28–4.14] for the same groups, respectively). Conclusions: Pancreatic fat predicts the future risk of metabolic syndrome.